Telemedicine for diabetic retinopathy screening in Croatia : a dream that could become a reality - Tomić, Martina, liječnica (Array, 2020)
Diabetic retinopathy (DR) is the leading cause of preventable blindness in working-age adults associated with devastating personal and socioeconomic consequences. The increasing use of anti-vascular endothelial growth factor (anti-VEGF) agents over the past decade and telemedicine implementation in systematic DR screening resulted in a decliningtrend of new blindness due to diabetes in several countries. Telemedicine is the remote delivery of healthcare services over the telecommunications infrastructure. It allows healthcare providers to evaluate, diagnose, and treat patients without the need for an in-person visit. Teleophthalmology is a telemedicine branch, mostly focused on diabetic retinopathy and retinopathy of prematurity. Screening for DR in Croatia is commonly performed annually, only by ophthalmologists using dilated slit-lamp biomicroscopic fundus examination. Due to the insufficient number of ophthalmologists and the lack of a formal call system, many diabetic patients do not perform annual screening. In an ideal DR screening model in Croatia, each diabetes center in university or general hospitals throughout Croatia (17 centers) would have one small digital fundus camera and an educated nurse who would perform dilated fundus photography. Electronic images from diabetes centers would be transferred for remote grading to the same hospitals’ ophthalmology departments or a central grading center for DR screening in Croatia. Grading for DR would be performed by an ophthalmologist, medical retina specialist. Patients would be annually invited by mail from the National Diabetes Registry to come to the nearest diabetes center for a fundus photographing and DR screening. Each patient with a positive result would be promptly referred to the medical retina specialist at the closest ophthalmology department for further examination and treatment.